PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI PADA CV. SAMPURNO ABADI - Ermawati, Juni (Performance, 2014)
This study aims to examine organizational cultures, motivation, compensation, and organizational commitment to employee performance in the private sector companies in the field of distribution and general trading. The study also examined whether organizational commitment mediates the organizational cultures, motivation and compensation to employee performance. The questionnaire were used as research data as much as 85 questionnaires were distributed to employees of the Division of Human Resources, Division of Accounting, Division of Vehicles and Marketing Division. Completed questionnaires (to be processed), 68 questionnaires (80.00%). The data collected were processed using the program path analysis SEM (Structural Equation Model) that is by using the method of PLS (Partial Last Square) to examine the direct and indirect influence of organizational cultures, motivation, compensation and organizational commitment to employee performance.The results of this study indicate that there is no direct influence of organizational cultures, motivation, and compensation on employee performance, but the commitment the organization has a direct influence on employee performance. Meanwhile, organizational cultures, motivation and compensation effect on employee performance through organizational commitment as an intervening variable.